Anti-Diabetic Activity Of Aqueous Extract Of Pithecellobium Dulce Benth Fruit Peel On Streptozotocin Induced Diabetic Rats (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The decoction of the Pithecellobium dulce fruit peel has been used for the control of diabetes mellitus in the traditional method adopted by the local people of northwest region of Tamil Nadu, India. The present study was carried out to investigate the anti-diabetic potential of aqueous extract of Pithecellobium dulce fruit peel by its oral administration (200 mg/kg) to streptozotocin-induced diabetic rats. The levels of blood glucose, urine sugar, glycosylated hemoglobin, glucose-6-phosphatase, fructose-1,6-bisphosphatase, total cholesterol, triglycerides, aspartate transaminase, alanine transaminase, alkaline phosphatase and reducedÂ  glutathione were increased significantly whereas the levels of plasma insulin, hexokinase, protein, liver glycogen, reduced glutathione, superoxide dismutase, catalase and glutathione peroxidase were decreased in streptozotocin-induced diabetic rats and it was normalized after treatment of aqueous extract. Glibenclamide was used as the standard drug. These outcomes suggest that the aqueous extract possesses anti-diabetic activity and supports the traditional use of the Pithecellobium dulce fruit peel decoction as hypoglycemic agent.